(untitled) (Bioscience Journal, 2018)
Studies related to environmental pollution, carbon monoxide levels and smoking need to be deepened, especially in the case of traffic workers. Therefore, the objective was to verify the association between environmental carbon monoxide and carboxyhemoglobin levels among smoking and non-smoking motorcycle taxi drivers. A longitudinal epidemiological study was carried out with 95 motorcycle taxi drivers with measurement of the environmental carbon monoxide, carboxyhemoglobin in the exhaled air in three moments with interval of six months, between June 2014 and March 2015, as well as sociodemographic and occupational characteristics of these workers. The seasons of the year presented different carbon monoxide averages (p <0.05), with higher levels in the spring and lower in the autumn, while carboxyhemoglobin levels among smokers and non-smokers were high in the winter, fair in the spring and low in the autumn. Statistical differences were observed between subgroups: between autumn and spring for non-smokers (p = 0.024) and between winter and autumn for smokers (p = 0.042). There was a positive correlation between carbon monoxide and carboxyhemoglobin levels for non-smokers (rs = 0.9983; p < 0.01). Environmental pollution represented different levels in the four seasons of the year and significant association with carboxyhemoglobin levels.Thecarboxyhemoglobin levels were higher among smokers, with statistical significance between winter and fall seasons, while non-smokers presented normal levels, whatconfirms the direct influence of tobacco in carboxyhemoglobin levels.